Profiling metal contamination from ultramafic sediments to biota along the Albanian shoreline of Lake Ohrid (Albania/Macedonia). (1st August 2021) - Minguez, Laetitia; Gross, Elisabeth M.; Vignati, Davide A.L.; Romero Freire, Ana; Camizuli, Estelle; Gimbert, Frédéric; Caillet, Céline; Pain-Devin, Sandrine; Devin, Simon; Guérold, François; Giambérini, Laure
Abstract: Ultramafic sediments exhibit high levels of geogenically-derived and potentially toxic metals, with Ni, Cr and Co often exceeding benchmark values. As yet, a holistic understanding of the bioavailability, mobility, potential ecotoxicity and trophic transfer of trace elements in both benthic and pelagic food chains in aquatic ultramafic environments (UME) is lacking. We investigated potential environmental health issues due to metal contamination by jointly implementing chemical, ecological and toxicological tools, along the Albanian shoreline of Lake Ohrid. It is an aquatic system of worldwide importance, representative of temperate UME with a legacy of Ni and Cr contamination from mining activities. Levels of Ni, Cr, Cd, Cu, Co, Fe, Mn and Zn were determined in waters, sediments and native biota. The potential environmental mobility of sediment-bound elements was further assessed using CaCl2, EDTA and acetic acid extractions. Whole-sediment ecotoxicity tests were also carried out using ostracods and chironomids, according to standardized procedures. Despite Ni and Cr concentrations above the sediment quality guidelines for probable effect levels, we did not observe ecotoxic effects in laboratory tests. However, these elements were bioavailable to native organisms under field conditions, especially to benthic primary producers in direct contact with sediments (up to 139 mg Cr kg −1 and 785 mg Ni kg −1 ). Although biomagnification was not observed, further investigations of metal translocation, metabolism and elemental trophic transfer along benthic food webs appears to be a general research priority in the management of temperate UME. The present study shows that proper management of temperate UME requires not only the integration of data from different lines of evidence, but also laboratory vs. field approaches to understand the subtler, long-term effects of increased elemental body burdens in native organisms. Highlights: Cr and Ni in sediments exceed probable effect levels by up to 3- and 11-fold respectively. Contaminated sediments did not cause ecotoxic effects in standard laboratory tests. Native biofilm and aquatic macrophytes accumulated large amounts of Ni and Cr. Trophic transfer was observed in some cases but without a risk of biomagnification. Managing ultramafic environments requires combination of chemical, toxicological and ecological tools.